Argel: entre realidad y ficción - Castellani, Jean-Pierre (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2010)
The city of Algiers constitutes a study case for the subject of “travelling through the city: urban faces and voices”, because it has suffered the superposition of different types of population and architectural styles. In this paper we try to study the consecutive realities and the different voices of the city.
Keywords: Space; Algiers; Western; Eastern; Representation